Review of Health Problems in Adult Patients with Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency - Reisch, Nicole (Experimental and Clinical Endocrinology & Diabetes, 2019)
The introduction of newborn screening programmes in most Western countries for classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency (CAH) enables timely introduction of life-saving glucocorticoid replacement in affected babies. Early diagnosis and optimised pediatric care not only successfully led to survival but also allow that almost all patients reach adulthood. Cohort studies in adults, however, provided evidence for significant health problems and co-morbidities of adult patients such as life-threatening adrenal crises, cardiovascular and metabolic health problems, fertility problems, benign endocrine tumours, and osteopenia and osteoporosis. This review summarises the current state of knowledge aiming to emphasize the neccessity of primary and secondary prevention of additional long-term health issues as a major task of health professionals in the care of CAH.
Keywords: congenital adrenal hyperplasia; 21-hydroxylase deficiency; adrenal androgens; adrenal crisis; fertility; testicular adrenal rest tumour; cardiovascular risk; bone health